'The iron rusted and decayed in our clubs': the failure of weightlifting in early twentieth-century Ireland. Issue 3 (3rd July 2021) - Heffernan, Conor
ABSTRACT: As a branch of sport history, the historiography of weightlifting lags behind other areas. The field is growing but much work needs to be done on its origins. Seeking to provide some context as to the origins of organised weightlifting in Europe, the following article uses Ireland as an ideal case study. The first two major efforts to form an Irish weightlifting organisation in the 1910s and early 1920s failed owing to a series of material and ideological problems. Exploring this point, the article begins with a discussion of weightlifting as an informal sport in Ireland in the nineteenth century before discussing the failure to establish an Irish weightlifting organisation in the early 1910s and early 1920s. Where one organiser, a Mr. W.A. MacPherson failed owing to a lack of material resources and a poor network of contacts, those following him, like the Irish weightlifter Michael Stokes, were hampered by warfare and political conflict. For historians of sport, a study of Irish weightlifting in this vein reiterates the many factors needed to establish formalised pursuits and serves as a timely reminder of the many barriers facing individual athletes wishing to compete.